Visible light photocatalytic performance and mechanism of highly efficient SnS/BiOI heterojunction - Juntrapirom S. (2017)
© 2017 Elsevier Inc. Novel SnS/BiOI heterostructures with excellent photocatalytic degradation of methyl orange were successfully prepared by a facile hydrothermal-coprecipitation method. The maximum methyl orange degradation activity under visible light irradiation (λ  >  400 nm) was found for 10 wt% SnS/BiOI. The composite also showed better stability and good recyclability compared to BiOI. The energy band diagram and band offsets from X-ray photoelectron spectroscopy investigation indicated that the novel composite was a type-II heterojunction where the photogenerated electron–hole can be efficiently separated and transferred. Results from UV–vis DRS, PL-TA and photocurrent response measurement suggested that the improved photodegradation efficiency of the SnS/BiOI heterojunction was mainly attributed to enhanced light absorption capability, strong ability to generate and transfer photoexcited charge carriers and high active species formation. Additionally, radical scavenging experiments demonstrated that holes and superoxide radicals are dominant active species, whereas hydroxyl radicals are of secondary importance in this system. A plausible photocatalytic mechanism of the SnS/BiOI composite was also discussed.